Fragmentation of maternal, child and HIV services: A missed opportunity to provide comprehensive care - Lyn J. Haskins; Sifiso P. Phakathi; Merridy Grant; Ntokozo Mntambo; Aurene Wilford; Christiane M. Horwood (AOSIS, 2016)
Background: In South Africa, coverage of services for mothers and babies in the first year of life is suboptimal despite high immunisation coverage over the same time period. Integration of services could improve accessibility of services, uptake of interventions and retention in care. Aim: This study describes provision of services for mothers and babies aged under 1 year. Setting: Primary healthcare clinics in one rural district in KwaZulu-Natal, South Africa. Methods: All healthcare workers on duty and mothers exiting the clinic after attending well-child services were interviewed. Clinics were mapped to show the route through the clinic taken by mother-baby pairs receiving well-child services, where these services were provided and by whom. Results: Twelve clinics were visited; 116 health workers and 211 mothers were interviewed. Most clinics did not provide comprehensive services for mothers and children. Challenges of structural layout and deployment of equipment led to fragmented services provided by several different health workers in different rooms. Well-child services were frequently provided in public areas of the clinic or with other mothers present. In some clinics mothers and babies did not routinely see a professional nurse. In all clinics HIV-positive mothers followed a different route. Enrolled nurses led the provision of well-child services but did not have skills and training to provide comprehensive care. Conclusions: Fragmentation of clinic services created barriers in accessing a comprehensive package of care resulting in missed opportunities to provide services. Greater integration of services alongside immunisation services is needed.